THE GODS' DELAY: OVID, HEROIDES 7.21 - Galfre, Edoardo (Classical Quarterly, 2024)
This note makes a new argument for van Lennep's conjecture di at Ovid, Heroides 7.21 against the manuscript reading te.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Aeneas; Dido; Heroides; intertextuality; Ovid; textual criticism